2018
DOI: 10.3390/molecules23112834
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom Substitution at Amide Nitrogen—Resonance Reduction and HERON Reactions of Anomeric Amides

Abstract: This review describes how resonance in amides is greatly affected upon substitution at nitrogen by two electronegative atoms. Nitrogen becomes strongly pyramidal and resonance stabilisation, evaluated computationally, can be reduced to as little as 50% that of N,N-dimethylacetamide. However, this occurs without significant twisting about the amide bond, which is borne out both experimentally and theoretically. In certain configurations, reduced resonance and pronounced anomeric effects between heteroatom subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 114 publications
(282 reference statements)
2
28
0
Order By: Relevance
“…It is important to mention that electrostatic potentials at the surface are represented by different colors, such as red, electron-rich; blue, electron-deficient; light blue, slightly electron-deficient; and yellow, slightly electronrich. The MEP analysis for amide 3 showed an electron-rich region around the carbonyl oxygen, whereas an electron-deficient region is located around the amide nitrogen; these findings are in good agreement with the resonance hybrid contributions in amides [36]. In addition, two green regions located around both 3,5-bis(trifluoromethyl)phenyl moiety and long aliphatic chain showed potential sites for lipophilic interactions.…”
Section: Molecular Electrostatic Potential (Mep) Mappingsupporting
confidence: 75%
See 2 more Smart Citations
“…It is important to mention that electrostatic potentials at the surface are represented by different colors, such as red, electron-rich; blue, electron-deficient; light blue, slightly electron-deficient; and yellow, slightly electronrich. The MEP analysis for amide 3 showed an electron-rich region around the carbonyl oxygen, whereas an electron-deficient region is located around the amide nitrogen; these findings are in good agreement with the resonance hybrid contributions in amides [36]. In addition, two green regions located around both 3,5-bis(trifluoromethyl)phenyl moiety and long aliphatic chain showed potential sites for lipophilic interactions.…”
Section: Molecular Electrostatic Potential (Mep) Mappingsupporting
confidence: 75%
“…The HOMO-LUMO energy gap and the pictorial illustration of HOMO and LUMO are shown in Figure 3. For the optimized structural models, the HOMO is located over the amide nitrogen (N2p z ), which indicates that the majority of charge transfer occurs between amide nitrogen and carbonyl carbon, in line with the resonance model in amides [36]. Furthermore, the LUMO is mainly located over the 3,5-bis(trifluoromethyl)phenyl moiety with a minor contribution of the π* C=O orbital, which indicates the small contribution of carbonyl oxygen to the LUMO.…”
Section: Frontier Orbitals and Global Reactivity Descriptorssupporting
confidence: 65%
See 1 more Smart Citation
“…Intramolecular hydrogen bonding to electron-deficient oxygen in N -pyramidalized bicyclic amides was reported by Otani, Ohwada and co-workers [57]. Excellent reviews on the role of amide bond activation in biological molecules [58], amidicity [59], and heteroatom substitution at amide nitrogen [60] have been published. Additional studies on the properties of amides have been reported [61,62].…”
Section: Miscellaneous Examplesmentioning
confidence: 99%
“…This catalytic strategy has been further explored by Garg [6][7][8][9][10][11][12][13] , Szostak [14][15][16][17][18][19][20] , and others [21][22][23][24][25][26][27][28][29] . Notably, amide bonds commonly need to be activated by electron-withdrawing groups, such as t-butoxycarbonyl (Boc), trifluoromethanesulfonyl (Tf), p-toluenesulfonyl (Ts), and cyclodicarbonyl group [30][31][32] . Despite these advances, direct organocatalytic activation of amide C-N bond, especially in an enantioselective manner, has yet to be achieved.…”
mentioning
confidence: 99%